2018
DOI: 10.4082/kjfm.17.0122
|View full text |Cite
|
Sign up to set email alerts
|

Serum Branched Chain Amino Acids Are Associated with Type 2 Diabetes Mellitus in Jordan

Abstract: BackgroundDiabetes mellitus is a global public health problem that is caused by the lack of insulin secretion (type 1) or resistance to its action (type 2). A low insulin-to-glucagon ratio predicts an increase in the serum levels of branched chain amino acids, a feature confirmed in several populations. This relationship has not been assessed in Jordan. The objective of this study was to investigate the association between serum branched chain amino acids and type 2 diabetes mellitus in patients in Jordan.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Dysregulation of plasma BCAAs was observed in multiple diseases, including GDM (16). Plasma BCAAs concentrations are different in different DM patients, which is useful to detect early DM (35), distinguish DM subtypes (16), and correlate with age, BMI, and ethnicity of patients (36, 37). The latest research suggests that normal or impaired glucose tolerance and T2DM groups have significant differences in BCAAs, and GDM has elevated plasma BCAAs (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysregulation of plasma BCAAs was observed in multiple diseases, including GDM (16). Plasma BCAAs concentrations are different in different DM patients, which is useful to detect early DM (35), distinguish DM subtypes (16), and correlate with age, BMI, and ethnicity of patients (36, 37). The latest research suggests that normal or impaired glucose tolerance and T2DM groups have significant differences in BCAAs, and GDM has elevated plasma BCAAs (38).…”
Section: Discussionmentioning
confidence: 99%
“…The measurement values of BCAAs were significantly different between the GDM group and the control group, and these differences were not found in the BMI < 28 kg/m 2 group. Differently, the latest research manifested that serum BCAAs levels were significantly higher in T2DM than those in controls in Jordan independent of age and BMI (37). However, Roy et al’s study (17) yielded BCAA concentrations combined with BMI and age may improve the diagnostic ability accuracy of GDM.…”
Section: Discussionmentioning
confidence: 99%
“…The power to detect the association between each allele and prediabetes was calculated using the Genetic Association Study (GAS) Power Calculator (). We assumed that the prevalence of prediabetes is 20% in Jordan [3]. In this study, the frequencies of alleles that were associated with higher risk of prediabetes were 0.35 (the T allele for rs1501299) and 0.79 (the A allele for rs266729).…”
Section: Methodsmentioning
confidence: 99%
“…The same study reported that 75% of DM patients live in countries of low-to-middle income, with the highest prevalence rates recorded in the Oceania and the Middle East and North Africa (MENA) regions [2]. An increased life expectancy together with a sedentary lifestyle and a Western-based diet are thought to be responsible for a DM epidemic in Jordan; a developing country in the MENA region [3]. In Jordan, the prevalence of DM has increased from 13% to 17% over a 10-year period (1994–2014) [4].…”
Section: Introductionmentioning
confidence: 99%
“…This was attributed to the restoration of underrepresented bacterial groups and bacterial metabolites in the patients. Insulin resistance has been associated with high levels of serum branched-chain amino acids [114,115] and an increased population of gut microbes such as Prevotella copri and Bacteroides vulgatus, which are known branched-chain amino acid producers [116]. The gut microbiota of T2DM patients has also been characterized by reduced butyrate-producing bacteria and high levels of opportunistic pathogens [117].…”
Section: Obesity and Type-2 Diabetes Mellitus (T2dm)mentioning
confidence: 99%